Dampak Pelatihan Elektrokardiogram Pada Kemampuan Perawat: Kajian Literatur Review - I Made Suarnada Saputra; Maria Astrid (Malahayati Nursing Journal, 2026)
ABSTRACT Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide. Nurses, as frontline healthcare providers, play a crucial role in the early detection and management of cardiac emergencies through their ability to interpret electrocardiograms (ECGs). However, limitations in nurses’ competency in ECG interpretation remain a significant challenge, highlighting the need for effective, evidence-based ECG training. This literature review aims to analyze the effectiveness of various electrocardiogram training methods in improving ECG interpretation skills among nurses and nursing students. This study employed a narrative literature review design using an evidence-based nursing (EBN) approach. Literature searches were conducted across several databases, including PubMed, Frontiers in Medicine, Nursing Open, Cureus, and BioMed Central. The included articles were published in English between 2020 and 2025, available in full text, and met the PICOT criteria. A total of 179 articles were initially identified, and after screening and selection based on inclusion and exclusion criteria, 15 articles were included for narrative analysis. The review findings indicate that various innovative ECG training methods—such as SAFMEDS, the CRISP method, flipped classroom, blended learning, simulation, and virtual reality—are more effective than conventional learning approaches. These methods significantly improve ECG interpretation accuracy, clinical competence, critical thinking skills, and both short-term and long-term knowledge retention. ECG training based on active learning strategies and technology has a significant positive impact on improving nurses’ ECG interpretation skills. The integration of evidence-based ECG training methods should be considered in nursing education and continuing professional development programs to enhance patient safety and clinical outcomes. Keywords: Electrocardiogram, ECG Training, ECG Interpretation, Nursing Competence.  ABSTRAK Penyakit kardiovaskular masih menjadi penyebab utama morbiditas dan mortalitas di dunia. Perawat sebagai tenaga kesehatan garda terdepan memiliki peran penting dalam deteksi dini dan penatalaksanaan kegawatan jantung melalui kemampuan interpretasi elektrokardiogram (EKG). Namun, keterbatasan kompetensi perawat dalam interpretasi EKG masih menjadi tantangan, sehingga diperlukan pelatihan EKG yang efektif dan berbasis bukti. Literature review ini bertujuan untuk menganalisis efektivitas berbagai metode pelatihan elektrokardiogram terhadap peningkatan kemampuan interpretasi EKG pada perawat dan mahasiswa keperawatan. Penelitian ini menggunakan desain narrative literature review dengan pendekatan evidence-based nursing (EBN). Pencarian literatur dilakukan melalui database PubMed, Frontiers in Medicine, Nursing Open, Cureus, dan BioMed Central. Artikel yang disertakan adalah penelitian berbahasa Inggris dengan rentang tahun 2020–2025, tersedia dalam bentuk full text, dan sesuai dengan komponen PICOT. Sebanyak 179 artikel teridentifikasi, dan setelah proses skrining serta seleksi berdasarkan kriteria inklusi dan eksklusi, diperoleh 15 artikel yang dianalisis secara naratif. Hasil review menunjukkan bahwa berbagai metode pelatihan EKG inovatif, seperti SAFMEDS, CRISP method, flipped classroom, blended learning, simulasi, dan virtual reality, terbukti lebih efektif dibandingkan metode pembelajaran konvensional. Metode-metode tersebut meningkatkan akurasi interpretasi EKG, kompetensi klinis, kemampuan berpikir kritis, serta retensi pembelajaran dalam jangka pendek maupun jangka panjang. Pelatihan EKG berbasis metode pembelajaran aktif dan teknologi memberikan dampak positif yang signifikan terhadap peningkatan kemampuan interpretasi EKG pada perawat. Integrasi metode pelatihan EKG berbasis bukti perlu dipertimbangkan dalam pendidikan keperawatan dan program pelatihan berkelanjutan guna meningkatkan keselamatan dan luaran pasien. Kata Kunci: Elektrokardiogram, Pelatihan EKG, Interpretasi EKG, Kompetensi Perawat.